2001
DOI: 10.1038/sj.jhh.1001242
|View full text |Cite
|
Sign up to set email alerts
|

Influence of different echocardiographic criteria for detection of left ventricular hypertrophy on cardiovascular risk stratification in recently diagnosed essential hypertensives

Abstract: Background: Hypertensive patients with left ventricular hypertrophy (LVH) need a prompter and more intensive pharmacological treatment than subjects without evidence of cardiac involvement. So the detection of LVH plays an important role for decision-making in hypertensives. Objective: To evaluate the impact of different echocardiographic criteria to define LVH in a more precise stratification of absolute cardiovascular risk in hypertensives without target organ damage (TOD) as assessed by routine investigatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2002
2002
2011
2011

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…Our study demonstrates that a larger proportion of subjects (48%) not requiring immediate treatment by the WHO/ISH guidelines would be reclassified at a higher CV risk after echocardiographic detection of LVH, suggesting that the impact of this diagnostic approach is more profitable in elderly than in younger hypertensives. 25 This evidence may be reasonably explained considering that both population-and selected hypertensive sample-based studies demonstrated that aging is an important factor associated with an increase in LV wall thickness, LV mass and prevalence of LVH. 28,29 Second, we have already underlined that this study was conducted on a relatively selected group of patients referred to a specialistic centre, and therefore the per cent shift toward a higher risk when echocardiographic data are added refers to the patients attending the hypertension hospital clinic only.…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…Our study demonstrates that a larger proportion of subjects (48%) not requiring immediate treatment by the WHO/ISH guidelines would be reclassified at a higher CV risk after echocardiographic detection of LVH, suggesting that the impact of this diagnostic approach is more profitable in elderly than in younger hypertensives. 25 This evidence may be reasonably explained considering that both population-and selected hypertensive sample-based studies demonstrated that aging is an important factor associated with an increase in LV wall thickness, LV mass and prevalence of LVH. 28,29 Second, we have already underlined that this study was conducted on a relatively selected group of patients referred to a specialistic centre, and therefore the per cent shift toward a higher risk when echocardiographic data are added refers to the patients attending the hypertension hospital clinic only.…”
Section: Discussionmentioning
confidence: 84%
“…First, our findings confirm the results of four previous studies investigating the impact of ultrasound cardiac and vascular examinations in selected hypertensive patients over a wide range of age, also showing that clinical evaluation based on simple routine work-up underestimates the overall cardiovascular risk in a significant proportion of them. [23][24][25][26][27] In a recent study by our group performed in 100 low-or medium-risk hypertensives (mean age 44 years), a percentage of patients, ranging from 9 to 25%, were found to have LVH according to different criteria, and consequently moved from low-and medium-risk strata to the high-risk stratum. 25 The Assessment of Prognostic Risk Observational Survey (APROS) study showed that 36.9% of 1074 hypertensive subjects seen in 44 hospital hypertension clinics, who were initially classified in the lower risk strata, according to WHO/ISH guidelines, Echocardiography in elderly hypertensives C Cuspidi et al changed their risk category to the higher one because of the echographic demonstration of LVH.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Elevated blood pressure associated with one or several risk factors cause progressively functional and structural changes with damage of heart and blood vessels [35][36][37].…”
Section: Table 3 Risk Factor Characteristics Derived From a Statisticalmentioning
confidence: 99%
“…Cardiovascular risk stratification only based on a simple routine work-up can often underestimate overall risk. 10 The recommended approach for initiation of treatment and for decision-making is not only based on BP level, but also on the presence or absence of target organ damage or other risk factors, allowing a much more accurate identification of high risk patients. 10 Many of the problems associated with lower socio-educational status can be eliminated with systems that overcome social and educational barriers to health care and to adoption of healthier lifestyles.…”
Section: Journal Of Human Hypertensionmentioning
confidence: 99%